Genotyping of HF crossbred cattle breeding bulls for A1/A2 variant of β-casein gene - TV Kulkarni; MP Sawane; VD Pawar; RS Deshmukh; Chopade MM; Ingle SA (Journal of Livestock Biodiversity, 2025)
The present study was carried out to genotype HF cross breeding bulls for A1/A2 variants of 13-casein gene was studied by collecting the blood samples of 49 breeding bulls from Frozen Semen laboratory, Kharki, Pune, Frozen Semen Lab, Aurangabad and Bombay Gorakshak Mandali, Mumbai. Genomic DNA was isolated from the blood samples by phenol-chloroform method. DNA fragments of 13-casein (CSN 2) gene were amplified by PCR using the suitable primers to amplify 121 bp products. PCR products were subjected for digestion with the DdeI restriction enzyme. After Restriction enzyme digestion the band pattern were observed on 4 per cents agar gel. The PCR-RFLP analysis revealed three band patterns (121bp, 86bp and 35bp) for A1A2 genotype and two band pattern (86bp and 35bp) for A2A2 genotype. The study showed two types of genotypes as A1A2 and A2A2 in the experimental population of HF crossbred breeding bulls. The genotype frequency of A1A2 and A2A2 was estimated as 65 and 35 per cent, respectively. Approximately gene frequency of A1 and A2 was calculated as 0.335 and 0.665, respectively. The present frequency status of A1 and A2 allele in the breeding bulls may be utilised for planning future breeding strategy in dairy cattle.